Custom architectures for fuzzy and neural networks controllers - Acosta, Nelson (2002)
Standard hardware, dedicated microcontroller or application specific circuits can implement fuzzy logic or neural network controllers. This paper presents efficient architecture approaches to develop controllers using specific circuits. A generator uses several tools that allow translating the initial problem specification to a specific circuit implementation, by using HDL descriptions. These HDL description files can be synthesized to get the FPGA configuration bit-stream.